A Woman with Dyke-Davidoff-Masson Syndrome: A Case Report - Fitriani Tri Rahayu; Hexanto Muhartomo; Aditya Kurnianto; Arinta Puspita Wati (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2025)
Introduction: Dyke-Davidoff-Masson Syndrome (DDMS) is a rare neurologic condition associated with drug-resistant epilepsy (DRE). Almost 100 DDMS cases were reported, and only 21 were reported among adults. This case report presented Dyke-Davidoff-Masson Syndrome in a 30-year-old woman. Case: A 30-year-old woman presented with generalized tonic-clonic seizures the day before admission. Each seizure lasted 5 minutes and reoccurred up to three times daily. She communicated but was slow in answering questions post-seizure. Neurological examination revealed left hemiparesis and contracture. Electroencephalography showed diffuse abnormalities. Brain magnetic resonance imaging (MRI) revealed DDMS with crossed cerebellar atrophy. Although anticonvulsant treatment controlled seizures, motor impairments like hemiparesis and joint contractures persisted since childhood. Discussion: DDMS is a cerebral palsy-related condition resulting from an injury associated with calvarium immaturity or childhood brain damage. Prenatal and post-natal injury may be the etiologic factors of DDMS. The clinical features of DDMS are cerebral hemiatrophy or hypoplasia, facial asymmetry, seizure, and contralateral hemiplegia with diverse combinations and severity. Specifically, in this case, the MRI showed right-sided brain atrophy, enlarged right lateral ventricle, and crossed cerebellar atrophy, all consistent with DDMS. Compensatory changes in the right skull, like thickened bones and enlarged frontal sinus, were also observed​. Symptomatic management is the mainstay of DDMS treatment, one of which is antiepileptic medication. Surgery is indicated as the last therapeutic option in some instances. Conclusion: DDMS cases in adults are rare. At present, there is no management algorithm for DDMS. Thorough history taking and physical and radiology examinations are required for DDMS diagnosis.